Civil War settlers : Scandinavians, citizenship, and American empire, 1848-1870 - Rasmussen, Anders Bo, 1978- (Cambridge University Press, 2022)
Civil War Settlers is the first comprehensive analysis of Scandinavian Americans and their participation in the US Civil War. Based on thousands of sources in multiple languages, that have to date been inaccessible to most US historians, Anders Bo Rasmussen brings the untold story of Scandinavian American immigrants to life by focusing on their lived community experience and positioning it within the larger context of western settler colonialism. Associating American citizenship with liberty and equality, Scandinavian immigrants openly opposed slavery and were among the most enthusiastic foreign-born supporters of the early Republican Party. However, the malleable concept of citizenship was used by immigrants to resist draft service, and support a white man's republic through territorial expansion on American Indian land and into the Caribbean. Consequently, Scandinavian immigrants after emancipation proved to be reactionary Republicans, not abolitionists. This unique approach to the Civil War sheds new light on how whiteness and access to territory formed an integral part of American immigration history.